UDEMY PLATFORM NON-FORMAL EDUCATION: ANALYSIS OF 3D-GRAPHICS COURSES - Volodymyr Hr. Shamonia; Mariia M. Ostroha; Ihor O. Biesiedin (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2019)
In view of the intensive development of visual content, the use of computer graphics by ordinary citizens is becoming more and more popular, which is possible in the context of non-formal education using open educational resources. The purpose of the research is: quantitative analysis of the open educational resources in the field of computer 3D graphics on the Udemy platform. The research objective is: 1) to describe the main thematic sections of the Udemy platform; 2) quantitative analysis of courses in 3D-graphics in terms of complexity, duration, language teaching, in areas of development of 3D graphics. The research methods are: terminological analysis for the interpretation of key research definitions; generalization of scientific sources for determining the priority directions of development of 3D-graphics and courses on its study; quantitative analysis of courses for their classification in directions. The research results. The Udemy platform not only offers its own educational content (about 200 thousand courses), but also offers teachers the ability to create author’s online courses from a large list of thematic sections: development of mobile applications, business, information technology and software, office software, personal growth, design, marketing, lifestyle, photography, health and fitness, music, teaching and academic disciplines. The section “Design” offers 1853 courses for studying 3D graphics: beginners are offered about 60% of courses; most courses are designed for 1-6 hours of study; about 10% of courses are offered with the receipt of a certificate on a free basis; the vast majority of courses (57%) are offered in English; the most popular 3D graphic program is Blender; about 12% of courses provide for a test of acquired knowledge and skills.